2019
DOI: 10.1111/imm.13148
|View full text |Cite
|
Sign up to set email alerts
|

How T'reg‐ulate healing of the injured spinal cord?

Abstract: Summary Regulatory T cells (Tregs) are important for limiting inflammation‐dependent damage in neural tissue. However, Tregs have also been shown to inhibit neural repair associated with type 2 (anti‐inflammatory/wound healing) immune responses. Recently, it was demonstrated that Sirtuins, a family of proteins that contribute to the control of cellular responses to metabolic stimuli, influence the functions of Tregs. Specifically, SIRT4 was found to suppress the anti‐neuroinflammatory activity of Tregs infiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…The recovery of olfactory function was associated with the increase of SIRT4 expression 27 . SIRT4 can inhibit the anti‐inflammatory activity of Tregs infiltrating the spinal cord after injury 28 . In the present study, we proved that the decreased TNF‐α, NLRP3, and IL‐1β caused by WY were elevated by siSIRT4.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The recovery of olfactory function was associated with the increase of SIRT4 expression 27 . SIRT4 can inhibit the anti‐inflammatory activity of Tregs infiltrating the spinal cord after injury 28 . In the present study, we proved that the decreased TNF‐α, NLRP3, and IL‐1β caused by WY were elevated by siSIRT4.…”
Section: Discussionsupporting
confidence: 61%
“…27 SIRT4 can inhibit the anti-inflammatory activity of Tregs infiltrating the spinal cord after injury. 28 In the present study, we proved that the decreased TNFα, NLRP3, and IL-1β caused by WY were elevated by siSIRT4. These results indicated that the regulation of inflammation by WY might be achieved through SIRT4.…”
Section: Bioinformatics Analysissupporting
confidence: 61%
“…The subpopulations of CD4 + T cells include helper T cells (Th1, Th2, and Th17) and regulatory T cells (Tregs) ( 90 ). T-cell infiltration in injured spinal cord tissues has been consistently reported in various SCI animal models ( 92 ). Jennifer et al.…”
Section: How Are the Functions Of Immune Cells And Immune Factors Orc...mentioning
confidence: 96%
“…In addition, Treg cells express the transcription factor FOXP3 in the nucleus, which is a major marker of Treg cell identity and a key molecule in the regulation of their function ( 113 , 114 ). Transforming growth factor β (TGF-β) and IL-10 are examples of the multiple inflammatory suppressive cytokines produced by Treg cells; these factors inhibit the activation and immune response of other cells, leading to immunosuppression and immunomodulation ( 115 , 116 ). Short-chain fatty acids (SCFAs) modulate Treg cells in the gut and affect the balance of Treg cells and IL-17+γδ T cells in the spinal cord, which has been reported to suppress inflammatory responses and promote locomotor function in SCI rats ( 111 ).…”
Section: Regulatory Role Of Treg Cells In Scimentioning
confidence: 99%